The Effectiveness of BDR (Learning From Home) in Improving Mathematic Thinking Ability through Open Ended Method in Early Chilhood Education - Rohmalina Rohmalina; Komala Komala (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2020)
This study aims to improve the Mathematical Thinking Ability of early childhood Using the Open-Ended Method, at Kartika Siwi Kindergarten Pusdikpal Cimahi. as the object of research, which consists of 20 children and was divided into two groups, namely the experimental group and the control group. In the experimental class the researcher gave treatment using open-ended media, while for the control group, the researcher gave treatment using ordinary learning using children's worksheets. (LKA). The research was started by conducting pretest and posttest in both groups.The results of this study are the use of open-ended methods can develop children's ability to improve mathematical thinking skills. The steps for using the successful open-ended method are as follows: (a). preparing the media before the child enters the room, (b) explaining in advance the activities to be carried out, (c) explaining the media to be used, (d) conditioning a pleasant atmosphere and providing a variety of supporting activities, (e ) counting by showing the blocks, (f) assigning children individually to arrange the numbers on the block, (g) giving motivation to children who are not yet capable.